2004
DOI: 10.1016/s1607-551x(09)70264-5
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Extracts of Cruciferous Vegetables

Abstract: The cruciferous vegetables cauliflower, broccoli, cabbage, Chinese radish, Chinese kale, and Chinese kitam were used in this study to prepare water-soluble and methanol-water extracts. Crude protein extracts were also obtained by diethylaminoethyl (DEAE) anion exchange chromatography. Water-soluble polysaccharides were prepared by ethanol precipitation followed by ultrafiltration. The antimicrobial effects of all these extracts were evaluated against Gram-positive bacteria, Gram-negative bacteria, and yeast. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 29 publications
4
42
0
1
Order By: Relevance
“…Many naturally occurring plants, including vegetables, have been shown to possess antibacterial activity and serve as a source of antibacterial agents against foodborne and food spoilage bacteria (Ali et al, 2001;Hu et al, 2004;Ayaz et al, 2008). In the present study, four different organisms were selected to check the antibacterial efficacy of vegetable extracts.…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many naturally occurring plants, including vegetables, have been shown to possess antibacterial activity and serve as a source of antibacterial agents against foodborne and food spoilage bacteria (Ali et al, 2001;Hu et al, 2004;Ayaz et al, 2008). In the present study, four different organisms were selected to check the antibacterial efficacy of vegetable extracts.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Ethanol, methanol and acetone and their aqueous mixtures are commonly used for the extraction purposes. Zhou & Yu (2006) (Kyung & Fleming, 1994;Hu et al, 2004;Ayaz et al, 2008) and antioxidant substance (Zhou & Yu, 2006;Andarwulan et al, 2010;Isabelle et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The highest stability and strongest antioxidant properties in red cabbage extract were assigned to anthocyanins [4]. Numerous studies have highlighted the potential importance of brassica vegetables as a source of antibacterial [5][6][7] and antioxidant substance [8][9][10]. Due to its antioxidant, anti-inflammatory and antibacterial properties, cabbage has widespread use in traditional medicine, in alleviation of symptoms associated with gastrointestinal diseases (gastritis, peptic and duodenal ulcers, and irritable bowel syndrome) as well as in the treatment of minor cuts and wounds and mastitis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported many antimicrobial peptides isolation from common vegetables and spices (Ngai and Ng, 2004;Hu et al, 2004;Oard et al, 2004;Xia and Ng, 2005;Ngai et al, 2005;Mariângela et al, 2006). Previous studies by our group have already described the isolation, characterization and antimicrobial nature of the protein isolated from Vigna radiata .…”
Section: Resultsmentioning
confidence: 99%